Managing fatigue after cancer treatment: development of RESTORE, a web‐based resource to support self‐management. Issue 8 (2nd February 2015) - Foster, C.; Calman, L.; Grimmett, C.; Breckons, M.; Cotterell, P.; Yardley, L.; Joseph, J.; Hughes, S.; Jones, R.; Leonidou, C.; Armes, J.; Batehup, L.; et al.
Abstract Objective The aim of this study is to co‐create an evidence‐based and theoretically informed web‐based intervention (RESTORE) designed to enhance self‐efficacy to live with cancer‐related fatigue (CRF) following primary cancer treatment. Methods A nine‐step process informed the development of the intervention: (1) review of empirical literature; (2) review of existing patient resources; (3) establish theoretical framework; (4) establish design team with expertise in web‐based interventions, CRF and people affected by cancer; (5) develop prototype intervention; (6) user testing phase 1; (7) refinement of prototype; (8) user testing phase 2; and (9) develop final intervention. Results Key stakeholders made a critical contribution at every step of intervention development, and user testing, which involved an iterative process and resulted in the final intervention. The RESTORE intervention has five sessions; sessions 1 and 2 include an introduction to CRF and goal setting. Sessions 3–5 can be tailored to user preference and are designed to cover areas of life where CRF may have an impact: home and work life, personal relationships and emotional adjustment. Conclusions It is feasible to systematically 'co‐create' an evidence‐based and theory‐driven web‐based self‐management intervention to support cancer survivors living with the consequences of cancer and its treatment. This is the first account of the development of a web‐based intervention to support self‐efficacy to manage CRF. An exploratory trial to test the feasibility and acceptability of RESTORE is now warranted. Copyright © 2015 John Wiley & Sons, Ltd.